Dignità umana e nuove tecnologie: La regolamentazione dell’ingegneria genetica nella Repubblica Popolare Cinese, tra valori tradizionali, modelli giuridici occidentali e nuovi orizzonti delle bioscienze - Novaretti, Simona (Dignità umana, 2024)
Building upon the case of genome-edited babies as a starting point, this article examines the significance attached to human dignity within Chinese culture as a whole, and within the legal structure of the People’s Republic of China in particular. Through the application of legal comparison methodologies, it endeavours to determine whether there exists a uniquely ‘Chinese-characterised’ comprehension of the concept, how it influences, if at all, the regulation of emerging technologies, and what potential trajectories might emerge.